Evaluation of Modified Frailty Index for Predicting Postoperative Outcomes after Upper Extremity Replantation and Revascularization Procedures - Desai, Anshumi; Luo, Angela; Borowsky, Peter A.; Bustos, Valeria P.; Fullerton, Natalia; Xu, Kyle Y.; Tadisina, Kashyap K. (Journal of Reconstructive Microsurgery, 2024)
Upper extremity (UE) replantation and revascularization are challenging surgical procedures, with survival rates being 50 to 90%. Preoperative risk stratification is challenging yet crucial as patients with comorbid conditions face increased complications. This study assesses the predictive value of the modified 5-item frailty index (5-mFI) for postoperative complications in these procedures.A retrospective study was done using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database (2011–2021) for UE replantation/revascularization. The 5-mFI score assigned points for comorbidities including pulmonary disease, heart failure, diabetes, hypertension, and functional status (0–5 scale; 1 point to each). 5-mFI scores stratified patients into <2 (low-risk) or ≥2 (high-risk) categories.Of 2,305 patients, the mean age and body mass index (BMI) were 53.13 years and 28.53 kg/m2, respectively. The 5-mFI ≥2 cohort experienced higher rates of all-cause complications, systemic complications, unplanned readmissions, and return to the operating room on univariate analysis. There was no significant difference in wound complication rates. Multivariable logistic regression showed that a higher 5-mFI was significantly associated with increased risks of all-cause mild and severe systemic complications. Wound complications, length of stay over 30 days, unplanned readmission, and return to the operating room were higher in high-risk patients, however not statistically significant.5-mFI is an effective tool for evaluating risk in UE replantation and revascularization, correlating high scores with significantly increased postoperative complications. High-risk patients with 5-mFI ≥2 also had more reoperations and readmissions. The use of 5-mFI in preoperative assessments can help personalize management, enhancing patient selection and care quality in these complex reconstructions.
Keywords: upper extremity; replantation; revascularization; modified 5-item frailty index; 5-mFI